2022
DOI: 10.3390/genes13112129
|View full text |Cite
|
Sign up to set email alerts
|

HEHR: Homing Endonuclease-Mediated Homologous Recombination for Efficient Adenovirus Genome Engineering

Abstract: Adenoviruses are non-enveloped linear double-stranded DNA viruses with over 100 types in humans. Adenovirus vectors have gained tremendous attention as gene delivery vehicles, as vaccine vectors and as oncolytic viruses. Although various methods have been used to generate adenoviral vectors, the vector-producing process remains technically challenging regarding efficacious genome modification. Based on our previously reported adenoviral genome modification streamline via linear–circular homologous recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Based on older developments [ 32 , 33 , 34 , 35 ], advanced recombineering techniques have recently been established [ 36 , 37 , 38 ]. The desired Ad genome can not only be cloned from purified virus preparations but also from virus infected cells [ 39 ].…”
Section: Adenoviruses and Their Vectorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on older developments [ 32 , 33 , 34 , 35 ], advanced recombineering techniques have recently been established [ 36 , 37 , 38 ]. The desired Ad genome can not only be cloned from purified virus preparations but also from virus infected cells [ 39 ].…”
Section: Adenoviruses and Their Vectorizationmentioning
confidence: 99%
“…Furthermore, it was recently demonstrated that double-strand break generated by CRISPR/Cas9 can highly increase the homologous recombination efficiencies in mammalian genomes [ 40 ]. In concert with our observation that homologous recombination from linear fragments promoted by the full-length Rac prophage protein RecET results in substantially higher cloning efficiency, we recently developed a strategy to convert the ccdB-mediated counter selection from linear–circular homologous recombination to linear–linear homologous recombination [ 38 ].…”
Section: Adenoviruses and Their Vectorizationmentioning
confidence: 99%
“…In a second step, the selection marker was removed and replaced by the desired sequence flanked by homology arms, coming either from an oligonucleotide in the case of point mutations or from PCR amplification when larger sequences needed to be inserted. This homologous recombination was performed in bacteria expressing the RecET recombinase system (26). Protocol 1 assembly backbone was obtained by replacing all HAdV-C5 sequences between the fiber gene and the right ITR with a PacI restriction site.…”
Section: Adenovirus Vectors Acquisitionmentioning
confidence: 99%